A patient with gastric cancer with peritoneal carcinomatosis treated with intraperitoneal chemotherapy who survived more than 5 years receiving repeated laparoscopic examinations: a case report. (December 2016) - Yamaguchi, Hironori; Kitayama, Joji; Ishigami, Hironori; Emoto, Shigenobu; Nishikawa, Takeshi; Tanaka, Junichiro; Tanaka, Toshiaki; Kiyomatsu, Tomomichi; Kawai, Kazushige; Hata, Keisuke; Nozawa, Hiroaki; Kazama, Shinsuke; et al.
Abstract Background Peritoneal dissemination of gastric cancer is still a dismal disease and has extremely poor prognosis even with systemic intensive chemotherapy. However, intraperitoneal chemotherapy using paclitaxel has recently shown good results. In order to perform optimal intraperitoneal chemotherapy, laparoscopic examination is necessary to assess the condition of peritoneal disseminated lesions. This is the first report of a case of a patient with gastric cancer with massive peritoneal metastasis treated with intraperitoneal administration of paclitaxel and repeated laparoscopic examinations who survived more than 5 years. Case presentation Here we report a case of a 60-year-old Japanese woman with peritoneal carcinomatosis of gastric cancer who underwent intraperitoneal chemotherapy receiving repeated laparoscopic examinations. The patient was referred to our institution for the treatment of peritoneal carcinomatosis of gastric cancer. The staging laparoscopy showed peritoneal metastasis in the whole peritoneal space with a peritoneal cancer index score of 23. An intraperitoneal access port was subcutaneously implanted. Paclitaxel was intraperitoneally and intravenously administered with oral administration of S-1. The second-look laparoscopy, which was performed after nine courses of intraperitoneal chemotherapy, revealed the disappearance of peritoneal carcinomatosis. A total gastrectomy with D2 lymphadenectomy was performed and intraperitoneal chemotherapy was continued after the surgery. The third laparoscopic examination, which was performed after 67 courses of intraperitoneal chemotherapy showed bilateral ovarian metastasis without recurrence of peritoneal carcinomatosis. Since multiple bone metastases developed after the third-look laparoscopy, bilateral adnexectomy was not performed and the chemotherapy was changed to the regimen including CPT-11. Our patient survived more than 5 years since the intraperitoneal chemotherapy started. Conclusions Sequential intraperitoneal chemotherapy could strongly suppress the development of peritoneal metastasis for several years. Repeated laparoscopic examinations are considered to be essential to evaluate the efficacy of intraperitoneal chemotherapy on peritoneal carcinomatosis of gastric cancer.